AGAMA SEBAGAI KOMODITAS DALAM PERSEBARAN HOAX DI ERA POST TRUTH - Nuril Hidayati (Jurnal Cakrawala Ilmiah, 2024)
Hoaxes have become part of human life and accompany life to this day. Moreover, in the post-truth era, hoaxes or fake news are increasingly easily recognized, produced, discovered and considered normal, where everyone uses technology in a modern space. This research is qualitative research to find a picture of religion as a hoax commodity in the post truth era. Post truth goes beyond truth in objectivity, religion as a hoax commodity as false news that has distorted the facts of religious truth and replaced it with lies for certain interests.